BAW Resonator as Elastic Characterization Tools of WO3 Thin Films. (2016) - Arab, M.; Dirany, N.; David, M.
Abstract: We report the elastic properties of tungsten trioxide WO3 films of various thicknesses using the dispersion behaviour of Balk Acoustic Wave BAW. Quartz crystal microbalance as well as BAW resonators are used for this purpose, allowing for the derivation of a reliable data set. WO3 films were characterized using X-ray diffraction, atomic force and scanning electron microscopy. The diffraction pattern showed crystallized layers with a pseudo cubic phase. The measured piezoelectric coefficient allowed fitting the model constants and obtaining the elastic coefficients and mass density.